Temporarily induced facial eczema by IL-17 inhibitors: a case report and literature review - Zhang, Ting; Meng, Fanzhang; He, Junchen; Li, Chen; Zhao, Zuotao (Frontiers in Allergy, 2025)
Biologics targeting interleukin-17 (IL-17) are widely used for moderate to severe psoriasis with great efficiency. Nonetheless, their usage has sporadically resulted in paradoxical reactions, such as eczema, sarcoidosis-like eruptions, alopecia areata, and pyoderma gangrenosum. Here, we report a case of temporary facial eczema to secukinumab with a score of 5 on the Naranjo scale, which suggests a probable drug side effect. The patient was a 32-year-old Chinese male with a history of chronic plaque psoriasis for 5 years. He was previously treated with topical steroids, calcipotriol, narrowband ultraviolet B phototherapy, and oral traditional Chinese medicine intermittently since 2020. In January of 2025, his psoriasis exacerbated and was not well controlled. The patient underwent an initial regimen of 300 mg secukinumab once weekly for 4 weeks, with significant psoriasis area and severity index (PASI) improvement, and was scheduled to continue maintenance therapy on a regimen of every 4 weeks. However, in the seventh week of the secukinumab treatment course, the patient's face developed diffuse, swollen, erythematous patches that had almost coalesced into sheets. The surface is smooth, without scales, blisters, or exudation, and accompanied by mild itching. Lab tests show elevated alanine aminotransferase (ALT) at 83.2 U/L (normal range: 9–50 U/L), slightly increased direct bilirubin at 8.48 μmol/L (normal range: 0–8.0 μmol/L). Other lab tests showed no significant abnormalities. After oral compound glycyrrhizin, olopatadine hydrochloride, triprolidine hydrochloride, and topical pimecrolimus for a week, his facial lesions were completely cleared. Liver function tests normalized following a 2-week course of polyenphosphatidylcholine. The patient delayed secukinumab administration by 2 weeks and continued 300 mg secukinumab administration on a regimen of every 4 weeks. No recurrence of similar rash or other adverse effects was observed during the subsequent follow-up period over 5 months. It is concluded that eczema could be induced temporarily by secukinumab, and maybe continued application.